Effect of Addition of Protein Fish Concentrates Cork (Channa striata) on Donuts Against Consumer Acceptance - Ridho Fadhlil Azmi; Desmelati '; N Ira Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was aimed to determine the effect of addition of snakehead fish (Channa striata) protein concentrate on donut so that the correct amount of addition of catfish protein concentrate was obtained on donut processing which preferred by consumers. The methode used in this research was experimental methode, with Completely Randomized Design (CRD) non factorial and 4 levels of treatment i.e., D1 (without addition of catfish protein concentrate), D2 (5% of catfish protein concentrate), D3 (10% of catfish protein concentrate), and D4 (15% of catfish protein concentrate) Parameter in test is acceptance of consumer test organoleptic (appearance, flavor, texture, aroma), and proximate analysis (water, protein, fat, and ash content The result of this research is the addition of 50g fish cork protein concentrate with the value of consumer acceptance to the likes (93.75%), the taste value (97.5%), the texture value (98.75%), and the aroma value (97.5%), With a water content of 21.37%, 9.78% protein content, 19.41% fat content, ash content 8.35%. Keywors: Donuts, KPI cork, donut KPI cork consumer acceptance